Ctotoxic and apoptogenic effects of Perovskia abrotanoides flower extract on MCF-7 and HeLa cell lines - Mohamad Ali Geryani; Davood Mahdian; Seyed Hadi Mousavi; Azar Hosseini (Mashhad University of Medical Sciences, 2016)
Objective: Perovskia abrotanoides Karel, belongs to the family Lamiaceae and grows wild alongside the mountainous roads inarid and cold climate of Northern Iran. The anti-tumor activity of P. abrotanoides root extract has been shown previously. This study was designed to examine in vitro anti-proliferative and pro-apoptotic effects of flower extract of P. abrotanoides on MCF-7 and Hela cell lines. Materials and Methods: Cells were cultured in DMEM medium with 10% fetal bovine serum, 100 units/ml penicillin and 100 µg/ml streptomycin and incubated with different concentrations of plant extracts. Cell viability was quantified by MTT assay. Apoptotic cells were determined using propidium iodide (PI) staining of DNA fragmentation by flow cytometry (sub-G1 peak). Results: P. abrotanoides extract inhibited the growth of malignant cells in a time and dose-dependent manner and 1000 µg/ml of extract following 48h of incubation was the most cytotoxic dose against Hela cell in comparison with other doses; however, in MCF-7 cells,1000 and 500 µg/ml PA induced toxicity at all time points but with different features.. Analysis of flowcytometry histogram of treated cells compared with control cells indicated that the cytotoxic effect is partly due toapoptosis induction. Conclusion: Hydro-alcoholic extract of P. abrotanoides flowers inhibits the growth of MCF-7 and HeLa cell lines, partly via inducing apoptosis. Their inhibitory effect was increased in a time and dose-dependent manner, especially in MCF7 cells. However, further studies are needed to reveal the mechanisms of P. abrotanoides extract-induced cell death.